1997
DOI: 10.1097/00006454-199710000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke as a risk factor for meningococcal disease

Abstract: Tobacco smoke exposure independently increases the risk of developing meningococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
2
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 23 publications
7
119
2
6
Order By: Relevance
“…A number of studies have shown associations between meningococcal disease and either smoking (FISCHER et al, 1997;COOKSON et al, 1998) or passive exposure to tobacco smoke (HANEBERG et al, 1983;STANWELL-SMITH et al. 1994: FISCHER et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown associations between meningococcal disease and either smoking (FISCHER et al, 1997;COOKSON et al, 1998) or passive exposure to tobacco smoke (HANEBERG et al, 1983;STANWELL-SMITH et al. 1994: FISCHER et al.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for meningococcal disease in industrialized countries include overcrowding (STANWELL-SMITH et al, 1994), passive exposure to tobacco smoke (HANEBERG et al, 1983;STANWELL-SMITH et al, 1994;FISCHER et al, 1997), kisses on the mouth (STANWELL-SMITH et al, 1994), preceding respiratory infections (CARTWRIGHT et al. 199 1: HARRISON et al.…”
Section: Introductionmentioning
confidence: 99%
“…The role of individual susceptibility and the presence of risk factors for the disease have been also widely studied. The presence of some immunodeficiencies [7,11,[19][20][21], special determinants in the host [22], tobacco consumption [23,24] and coinfections with another respiratory diseases [25][26][27][28], among others factors, have been associated to the meningococcal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking has also been associated with an increased risk for both respiratory (6,7) and nonrespiratory (8) infections in the general population. Active smoking has been reported in up to 14.2% of individuals undergoing hemodialysis (9), a population that experiences an excessively high mortality rate.…”
Section: Introductionmentioning
confidence: 99%